2012
DOI: 10.2147/opth.s29758
|View full text |Cite
|
Sign up to set email alerts
|

Corneal topographic changes following trans-conjunctival 20 gauge sutureless vitrectomy (TC20V)

Abstract: PurposeTo assess the occurrence and magnitude of corneal topographic changes in phakic eyes undergoing Transconjuctival Cannulated 20 gauge Vitrectomy (TC20V) without scleral buckling or silicone oil tamponade.SettingProspective randomized controlled study done at Egyptian Eye Academy.MethodsForty eyes of 40 patients underwent TC20V for a variety of vitreo-retinal conditions over a 1 year follow-up period. Corneal keratometric readings were obtained using Oculus Pentacam before surgery, 1 week after, and 1 mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Despite the fact that to our knowledge no recent studies have tackled the same variables, our hypothesis was inspired based on older studies which stated that, after strabismus surgery, corneal topographic changes were likely to occur [ 8 , 9 , 15 ]. In other studies, transient corneal topographic changes were found to occur after sutureless vitrectomy as well [ 11 , 12 ]. These changes occurred despite the lack of direct tissue continuity between the cornea and the vitreous body.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Despite the fact that to our knowledge no recent studies have tackled the same variables, our hypothesis was inspired based on older studies which stated that, after strabismus surgery, corneal topographic changes were likely to occur [ 8 , 9 , 15 ]. In other studies, transient corneal topographic changes were found to occur after sutureless vitrectomy as well [ 11 , 12 ]. These changes occurred despite the lack of direct tissue continuity between the cornea and the vitreous body.…”
Section: Discussionmentioning
confidence: 86%
“…Recent studies found mild corneal topographic changes after sutureless vitrectomy as well, that most of these changes however, decayed with time [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The primary advantages of sutureless vitrectomy are shorter operative times [16,17,18,19,20,21,22], less inflammation and pain postoperatively [15,17,19,20,23,24], and improvement in patient comfort [25,26,27]. Astigmatism following transconjunctival sutureless vitrectomy is uncommon [28,29,30,31] and, when present, is less important than in 20-gauge standard vitrectomy cases [32,33,34]. The fact that no sutures are placed in the sclera results in a reduction in postoperative astigmatism.…”
Section: Discussionmentioning
confidence: 99%